2018
DOI: 10.3892/ol.2018.9849
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cytokine‑induced killer cells targeting CD40 and GITR

Abstract: Since the publication of a novel protocol in 1991, cytokine-induced killer (CIK) cells have shown promising results in the treatment against neoplastic diseases. Despite ongoing preclinical and clinical studies, CIK cell treatment in the context of human monoclonal antibodies targeting tumor-necrosis factor receptors remains overlooked. The present study investigated whether a combination of CIK cells with human monoclonal antibody anti-CD40 and anti-Glucocorticoid-induced TNF-related protein (GITR) would lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…After cell harvesting, the proportion of CD3 + CD56 + (CIK) cells, CD3 − CD56 + (NK) cells and CD3 +/− CD56 + (CIK/NK) cells was detected by flow cytometry. The proportion of CIK cells are a group of immune effector cells characterized by the cell surface marker CD3 − CD56 + and the proportion of NK cells are a type of lymphocytes, which are distinguished by the cell surface marker CD3-CD56+ (39). Both CIK and NK cells play critical role in immune anti-tumor effect (40).…”
Section: Methodsmentioning
confidence: 99%
“…After cell harvesting, the proportion of CD3 + CD56 + (CIK) cells, CD3 − CD56 + (NK) cells and CD3 +/− CD56 + (CIK/NK) cells was detected by flow cytometry. The proportion of CIK cells are a group of immune effector cells characterized by the cell surface marker CD3 − CD56 + and the proportion of NK cells are a type of lymphocytes, which are distinguished by the cell surface marker CD3-CD56+ (39). Both CIK and NK cells play critical role in immune anti-tumor effect (40).…”
Section: Methodsmentioning
confidence: 99%
“…Biederbick et al recently contributed to raise concerns about synergistic molecular mechanisms of CIK cells by using a combination of anti-CD40 and anti-GITR mAb in the human lymphoma cell lines SU-DHL-4 and Daudi (both CD40-positive) [ 60 ]. More recently, Li et al reported an increase in IFN-γ secretion in B-NHL cell lines treated with CIK alone or with the PD-1 antibody, yet this trend was not observed for PD-L1, raising the question of whether PD-1 and PD-L1 are comparable and interchangeable in the clinical practice [ 61 ].…”
Section: Improving Cik Cell Therapy On Lymphomamentioning
confidence: 99%